Effect of SNPs in HSP Family Genes, Variation in the mRNA and Intracellular Hsp Levels in COPD Secondary to Tobacco Smoking and Biomass-Burning Smoke - Ambrocio-Ortiz, Enrique; Pérez-Rubio, Gloria; Ramírez-Venegas, Alejandra; Hernández-Zenteno, Rafael; Del Angel-Pablo, Alma D.; Pérez-Rodríguez, Martha E.; Salazar, Ana M.; Abarca-Rojano, Edgar; Falfán-Valencia, Ramcés (Frontiers in Genetics, 2020)
Heat shock proteins (HSP) genes are a superfamily responsible for encoding highly conserved proteins that are important for antigen presentation, immune response regulation, and cellular housekeeping processes. These proteins can be increased by cellular stress related to pollution, for example, smoke from biomass burning and/or tobacco smoking. Single nucleotide polymorphisms (SNPs) in these genes could affect the levels of their proteins, as well as the susceptibility to developing lung diseases, such as chronic obstructive pulmonary disease (COPD), related to the exposure to environmental factors. Methods: The subjects included were organized into two comparison groups: 1,103 smokers (COPD patients, COPD-S = 360; smokers without COPD, SWOC = 743) and 442 never-smokers who were chronically exposed to biomass smoke (COPD patients, COPD-BS = 244; exposed without COPD, BBES = 198). Eight SNPs in three HSP genes were selected and genotyped: four in HSPA1A, two in HSPA1B, and two in HSPA1L. Sputum expectoration was induced to obtain pulmonary cells and relative quantification of mRNA expression. Subsequently, the intracellular protein levels of total Hsp27, phosphorylated Hsp27 (Hsp27p), Hsp60, and Hsp70 were measured in a sample of 148 individuals selected based on genotypes. Results: In the smokers’ group, by a dominant model analysis, we found associations between rs1008438 (CA+AA; p = 0.006, OR = 1.52), rs6457452 (CT+TT; p = 0.000015, OR = 1.99), and rs2763979 (CT+TT; p = 0.007, OR = 1.60) and the risk to COPD. Among those exposed to biomass-burning smoke, only rs1008438 (CA+AA; p < 0.01, OR = 2.84) was associated. Additionally, rs1008438 was associated with disease severity in the COPD-S group (AA; p = 0.02, OR = 2.09). An increase in the relative expression level of HSPA1A was found (12-fold change) in the COPD-BS over the BBES group. Differences in Hsp27 and Hsp60 proteins levels were found (p < 0.05) in the comparison of COPD-S vs. SWOC. Among biomass-burning smoke-exposed subjects, differences in the levels of all proteins (p < 0.05) were detected. Conclusion: SNPs in HSP genes are associated with the risk of COPD and severe forms of the disease. Differences in the intracellular Hsp levels are altered depending on the exposition source.